Assessment of left ventricular performance and myocardial viability using quantitative radioisotope techniques. Issue 2 (August 1979) - Pachinger, O; Ogris, E; Probst, P; Joskowics, G; Sochor, H; Kaindl, F
Abstract : The diagnostic value of a combined radionuclide technique was compared with conventional angiocardiographic techniques in 60 patients with coronary artery disease. Quantitative 201Tl myocardial imaging combined with radionuclide angiocardiography using 99mTc-HSA provided a safe and accurate method for the assessment of left ventricular performance. The defects on the 201Tl images correlated with the severity of asynergy seen on the contrast ventriculogram. Static imaging alone distinguished hypokinetic from akinetic or dyskinetic areas. However, using both tracer techniques, akinesis could bedistinguished from dyskinesis. In patients with disturbed left ventricular function, cardiac transit times correlated with haemodynamic changes, and left ventricular ejection fraction was the most sensitive index. Thus, this combined radionuclide approach provides data for the evaluation of overall and regional wall function. A major advantage of this non-invasive auantitative technique is its applicability to the critically ill patient at the bedside.